The role of mosquito predators in the ecosystem in reducing the incidence of dengue - Nawab, Kamaruzaman Khan; Rasdi, Irniza (Life Sciences Society of Pakistan, 2019)
The aim of this study was to show that the presence of mosquito predators in the ecosystem decreased the incidence of dengue cases. Data was obtained by daily inspection of 85 Aedes mosquito potential breeding point at 15 dengue outbreak hotspot localities with at least one mosquito predator present at the locality and the VEKPRO programme used in the monitoring of dengue cases in Malaysia. The mosquito predators identified were dragonfly, dragonfly nymph, gambushia fish, tadpole and frog. The study was done at the district of Petaling from 4th January, 2015 to 4th July 2015. The results show that the presence of mosquito predators hinder the breeding of Aedes mosquito in the ecosystem which is related to a decrease in dengue cases.